Regulation through “bricking”: private ordering in the “Internet of Things” - Natasha Tusikov (Internet Policy Review)
Internet-enabled “smart products” operate through networked software that links the devices to their manufacturers’ servers to enable the collection and distribution of data, and, as a result, these products are vulnerable to software disruption. This article examines “regulation by bricking”, which refers to the deliberate impairment or destruction of software with the intention of negatively affecting product functionality. The article argues that companies are employing bricking within a system of private ordering that is reshaping the governance of physical objects, as companies can arbitrarily and remotely affect the functionality of any software-enabled device and even determine product’s lifespan. Further, the article contends that through companies’ post-purchase regulation of internet-connected goods, “Internet of Things” (IoT) firms have an unfair capacity to impose their preferred policies unilaterally, automatically, and remotely. Control over software thus enables control over hardware. This private ordering occurs within a regulatory framework in which IoT companies use restrictive licensing agreements to govern the use of the products’ software. With a focus on the governance of consumer-oriented IoT goods within the United States, the article draws upon the law and technology literature to explain bricking as a form of techno-regulation, which is the deliberate use of technology as a regulatory instrument (Brownsword, 2005), through an analysis of manufacturers’ licensing agreements for smart products.